Penentuan Kadar Albumin Ikan Gabus (Channa striata) dengan Metode Biuret setelah Dikukus dan Dipepes: Determination of Albumin Content of Snakehead Fish (Channa striata) by Biuret Method after Steamed and Wrapped - Inda Hastuti N Naser; Syaiful Bahri; Pasjan Satrimafitrah; Abd. Rahman Razak; Ruslan; Ahmad Ridhay; Dwi Juli Puspitasari; Khairuddin (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Snakehead fish (Channa striata) is a type of freshwater fish that contains high levels of protein albumin. The research was conducted to determine the albumin content in snakehead fish after the cooking process, both steamed and wrapped. The research was conducted using a completely randomized design with a factorial pattern, the first factor was the cooking method (steamed and wrapped) and the second was cooking time (10, 15, 20, and 20 minutes). Determination of protein albumin levels in snakehead fish after processing using the Biuret method. The steaming process for 15 minutes resulted in protein content in the snakehead fish of 0.76%, while the protein albumin that was lost was 19.28%. The wrapped method for 20 minutes has a remaining protein content of 0.59%, while the missing protein is 38.78%. The method of processing snakehead fish by steaming is better than the wrapping process.